Institutional contexts of political conflicts around free movement in the European Union: a theoretical analysis - Ruhs, M; Palme, J (Routledge, 2018)
The Member States of the European Union (EU) have been engaged in highly divisive debates about whether and how to reform the rules for the ‘free movement’ of EU workers and their access to national welfare states. While some countries have argued for new restrictions on EU workers’ access to welfare benefits, many others have opposed policy change. What explains EU Member States’ different policy positions on this issue? Existing accounts have focused on populist political parties and the media. In contrast, this article provides a theoretical institutional analysis of how cross-country differences in the regulation of national labour markets and welfare states can contribute to divergent national policy responses to free movement. We argue and explain how labour market and welfare state institutions can affect national policy actors’ positions on free movement directly, and/or indirectly via inter-actions with normative attitudes and the characteristics of EU labour immigration.